The prevalence and levels of enteric viruses in groundwater of private wells in rural Alberta, Canada. (1st September 2021) - Pang, Xiaoli; Gao, Tiejun; Qiu, Yuanyuan; Caffrey, Niamh; Popadynetz, Jessica; Younger, John; Lee, Bonita E.; Neumann, Norman; Checkley, Sylvia
Highlights: Studying virus contamination of water in 62 private wells in rural Alberta through serial sampling. Prevalence of enteric viruses was very low and sporadic in groundwater. Adenovirus and rotavirus were detected most frequently among others. Well setting for different uses was not related to presence of the viruses. Analyzing effect of well characteristics on occurrence of viruses in groundwater. Abstract: The prevalence and levels of enteric viruses in untreated groundwater of private wells used for drinking and/or agricultural practices in rural Alberta were studied using the qPCR panel assay, integrated cell culture with qPCR and cell culture in the volume of 500 liters per sample through serial sampling. Seven viruses were assessed including adenovirus, rotavirus, norovirus, astrovirus, sapovirus, reovirus and JC virus. Five viruses were detected with an overall positive detection rate of 6.33 % (45 of 711 samples). The most frequently detected virus was adenovirus (48.9%, 22/45) followed by rotavirus (44.4%, 20/45), reovirus (20%, 9/45), JC virus (6.7%, 3/45) and norovirus (6.7%, 3/45). There was no significant difference in the positive detection rates, ranging from 1.1% to 3.4% by various well settings used for broiler farms, cow/calf farms, feedlots and rural acreages. Effects of well characteristics (aquifer type, well depth, static level of water, well seal) and well completion lithology on potential viral contamination of groundwater of private wells were also analyzed upon available data. The findings demonstrate that occurrence of enteric viruses is low and viral contamination is sporadic in groundwater of private wells in rural Alberta. Conventional fecal bacterial indicators (coliform and/or E. coli ) were not a representative marker for viral contamination in groundwater wells in rural Alberta. Graphic abstract: Image, graphical abstract